CARI PARANDUAK DALAM PERSPEKTIF HUKUM ISLAM (Sebuah Tradisi di Kabupaten Solok Sumatera Barat) - Sobhan, Sobhan; Hamro, Ustini (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2023)
Another fish is different, according to a quote from an Indonesian proverb that describes the diversity of tribes and customs in society. In the hundreds of ethnic groups in Indonesia, of course, there are as many customs; some have a correlation with one another, and some do not correlate at all. Some even tend to conflict with each other. In this regard, this article will try to explain the existence of the Cari Paranduak tradition of the community in Nagari Sungai Nanam, Solok Regency, which is a cultural treasure of the nation and deserves to be known, as well as look at it from the perspective of Islamic law. This research is qualitative research by collecting data from the field and in-depth interviews with informants. The informants for this research were five Datuak Nagari Sungai Nanam people. Those were selected using a purposive sampling technique. This research will explain the origins of the cari paranduak tradition in Nagari Sungai Nanam, its implementation, and the view of Islamic law towards the cari paranduak tradition in Nagari Sungai Nanam, Solok Regency. Based on the research results, it has implications for strengthening Minangkabau customs with the ABS-SBK philosophy (Adat Basandi Syarak, Syarak Basandi Kitabullah), in all matters, especially in the Cari Paranduak tradition.